VOKAL BAHASA BUDONG-BUDONG - Mardi Nugroho (Kantor Bahasa Kepulauan Riau, 2018)
The Budong-Budong language is an almost extinct language. Number of speakers of Budong-Budong language are 70 people. Therefore, this language should be prioritized for conservation. The efforts included in the conservation programe are the preparation of phonological, morphological, syntactic, and literary or orthographic systems. The problem of the research is to know any vowels are available in Budong-Budong language. The purpose of this research is to find vowels contained in Budong-Budong language and their allophones that are expected to be useful for any preparation of its phonology system. The method used in this research is descriptive. Data collection is done by interview and recording. Data processing is done by the method of matching (referent and opponent referral tool) and the method of distribution (with the technique of minimal pair opposition). This study refers to the theory of Verhar on the concept of phonemes, vowel types, and the identity of phonemes as distinct identities. The result of data analysis is vowels in Budong-Budong as much as five, that are / i /, / e /, / a /, / o /, and / u /. There is a special vowel in Budong-Budong language, i.e. /a/. The /a/ vowel of Budong-Budong has two allophones, i.e. [a] and [_]. The examples of allophone [a] are such as in the following words: /ako/ [ako] ‘what’, /babuah/ [babu:ah] ‘chest’, and /bulampa/ [bulampa] ‘thigh’. The examples of allophone [_] are such as in the following words: /aso?/ [_So?] ‘rib’, /kanding/ [k_ndiG] ‘forehead’, dan /lima/ [lim_] ‘five’. AbstrakBahasa Budong-Budong merupakan bahasa yang hampir punah. Bahasa Budong-Budong jumlah penuturnya 70 orang. Oleh karena itu, bahasa ini selayaknya diprioritaskan untuk dikonservasi. Contoh upaya yang termasuk dalam program konservasi ialah penyusunan sistem fonologi, morfologi, sintaksis, dan sistem aksara atau ortografi. Masalah dalam penelitian ini ialah vokal apa saja yang terdapat dalam bahasa Budong-Budong. Tujuan penelitian ini ialah menemukan vokal-vokal yang terdapat dalam bahasa Budong-Budong dan alofon-alofonnya yang diharapkan berguna dalam upaya penyusunan sistem fonologinya. Metode yang digunakan dalam penelitian ini bersifat deskriptif. Pengumpulan data dilakukan dengan wawancara dan perekaman. Pengolahan data dilakukan dengan metode padan (alat penentunya referen dan lawan bicara) dan metode distribusional (dengan teknik oposisi pasangan minimal). Penelitian ini mengacu pada teori Verhar mengenai konsep fonem, jenis-jenis vokal, identitas fonem sebagai identitas pembeda. Hasil analisis data ialah vokal dalam bahasa Budong-Budong sebanyak lima, yaitu /i/, /e/, /a/, /o/, dan /u/. Ada vokal yang khas dalam bahasa Budong-Budong, yaitu /a/. Vokal /a/ memiliki dua alofon, yaitu [a] dan [_]. Contoh alofon [a] ialah pada kata-kata /ako/ [ako] ‘apa’, /babuah/ [babu:ah] ‘dada’, dan /bulampa/ [bulampa] ‘paha’. Contoh alofon [_] ialah pada kata-kata /aso?/ [_So?] ‘rusuk’, /kanding/ [k_ndiG] ‘dahi’, dan /lima/ [lim_] ‘lima’.